Human Capital, Tangible Wealth, and the Intangible Capital Residual - Hamilton, Kirk; Liu, Gang (World Bank, Washington, DC, 2013)
Since income is the return on wealth, the total wealth of any given country should be on the order of 20 times its gross domestic product. Instead the average observed ratio from the balance sheet accounts of the System of National Accounts is a factor of 2.6 to 6.6, depending on whether natural resource stocks are included in the balance sheet. The clear implication is that the System of National Accounts wealth accounts are incomplete, with the most obvious omission being human capital. Estimating the value of human capital using the lifetime income approach for a sample of 13 (mostly high-income) countries yields a mean share of human capital in total wealth of 62 percent -- four times the value of produced capital and 15 times the value of natural capital. But for selected high-income countries in the sample there is still an average of 25 percent of total wealth that is unaccounted -- it is neither produced, nor natural, nor human capital. This residual intangible wealth is arguably the "stock equivalent" of total factor productivity -- the value of assets such as institutional quality and social capital that augment the capacity of produced, natural and human capital to support a stream of consumption into the future.